Drying Vanilla Using A Hybrid Dryer - Warji, Warji; Tamrin, Tamrin; Kuncoro, Sapto; Lanya, Budianto; Muzaqi, Hani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Vanilla (Vanilla planifolia Andrew) is a plant that has high economic value; the plant is oriented for export. Postharvest handling is necessary to produce good quality vanilla; One of them is the drying process. This study aims to measure the drying time of vanilla, measure the decrease in moisture content, and analyze the efficiency of drying wet vanilla using a rack-type hybrid dryer. The research was conducted with three treatments, namely: drying using solar energy, drying using electrical energy, and drying using solar energy and electrical energy (hybrid). Based on the results of the study, it was found that drying using solar energy, drying using electrical energy, and drying using solar energy and electrical energy (hybrid) took 15 days, 17 days, and 13 days, respectively. The initial moisture content of drying is about 91.25% which decreases to about 32.44% at the end of drying. The efficiency of the three treatments was 6.39%, 1.58%, and 0.92%, respectively. Keywords: Drying, Hybrid postharvest, Vanilla